Penerapan Teknik Reward and Punishment dalam Pembentukan Lingkungan Bahasa Arab di Pesantren Fathul Hidayah Lamongan - Linda Widiyawati; M. As'ad Nahdly; Muh Sabilar Rosyad (LUGHATI: Jurnal Pendidikan Bahasa Arab, 2023)
The Fathul Hidayah Pangean Lamongan Islamic Boarding School is one of the ?educational institutions that implements a mandatory foreign language ?program, including Arabic and English. Based on initial observations, the use of ?Arabic in daily life is still not optimal. Therefore, stakeholders in the Islamic ?boarding school environment strive to strengthen the language environment ?through reward and punishment techniques. This research aims to find out how ?reward and punishment techniques are applied in forming an Arabic language ?environment, as well as uncovering supporting factors and obstacles to the ?application of these techniques in forming an Arabic language environment. ?Researchers used a qualitative approach with a descriptive study type. Data ?comes from several stakeholders in Islamic boarding schools and schools as ?well as some MTs grade 8 female students. Researchers used observation ?techniques, in-depth interviews and documentation. Data analysis uses ?interactive descriptive techniques whose validity has previously been tested ?through continuous observation techniques, source triangulation, and peer ?interpretation. The results of this research are: 1) the application of reward ?techniques is carried out using various models, including verbal and non-verbal, ?such as applause, cheers, praise and prayer, even on certain events the form of ?reward can be in the form of a plaque, gift or gift. Present. Meanwhile, there are ?also various forms of punishment, all of which are educational punishments and ?not physical punishments, such as memorizing vocabulary, translating, making ?sentences and even essays; 2) Supporting factors for implementing reward and ?punishment techniques include motivation from teachers, leaders, supervisors, ?Islamic boarding school administrators, facilities and infrastructure, support for ?language acquisition and learning. Meanwhile, the inhibiting factors are the ?diversity of each individual's language abilities, as well as some students who ?are less than responsible in carrying out Islamic boarding school discipline, and ?there are even some administrators who should be able to set an example in ?Arabic who commit language violations.